Esporte no contexto escolar: estudo do perfil dos professores de educação física qua atuam como técnicos nas olimpíadas estudantis no município de São Paulo - Nunes, Hudson Fabricius Peres [UNESP] (2015)
This study aimed to establish relations and comprise if there is consistency between the profile of curriculum graduation and sports conception of the teachers-coaches finalists of the Students Olympics (OE) in the city of São Paulo in relation to Nacional Curriculum Guidelines (DCNs), that guide the College Institutions (IES) to define the profile of formation of the bachelor degree in Physical Education based on Resolutions CNE/CP n. 01 and 02/02, Law of Directives and Bases (LDB), National Curriculum Parameters (PCNs) and the More Education Program, and simultaneously, the relationship between teachers-coaches profile with school sports of promoted income by the OE and Athlete in School Program, according to the regulations of Decree n. 7.984/13. The methodology used is based in qualitative research, being splited into two stages: I) exploratory phase: use of documentary sources and bibliography review; II) descriptive phase: characterization of the profile of curriculum formation and profile description of sports conception of teachers-coaches, using as investigation instrument the almost structured questionnaire and as technique the content analysis. Before the presented objectives, it was established that the studied profile hold curriculum formation predominant in the resolutions CFE n. 69/69 and 03/87, with exception of four participants formed under surveillance of the current DCNs with the baccalaureate degree graduation subsequent to bachelor. The profile of curriculum formation of the teachers-coaches approach to the characteristics of traditional-sports curriculum. In conclusion, the profile of sports graduation and conception predominant of the teachers-coaches of OE is coherent with the objectives of the Ministry of Sport in promoting the school sport, detect talent and shape them sportily through the School Games and Athlete in School Program, according to the regulations of Decree n. 7.984/13, and at the same time, is ...